Kinetics of Torque Teno Virus Viral Load Is Associated with Infection and De Novo Donor Specific Antibodies in the First Year after Kidney Transplantation - Querido, Sara (2023)
Torque teno virus (TTV) was recently identified as a potential biomarker for the degree of immunosuppression, and potentially as a predictor of rejection and infection in solid organ transplant patients. We evaluated TTV viral load in kidney transplant (KT) patients during the first year post-transplant to examine overall kinetics and their relationships with deleterious events, including episodes of infection and the formation of de novo donor-specific antibodies (DSAs). In a single-center, prospective observational cohort study, 81 KT patients were monitored at baseline, week 1, and month 1, 3, 6, 9 and 12, post-KT, and whenever required by clinical events. Kidney function, plasma TTV load, immunoglobulins and lymphocyte subpopulations were assessed at each time point. Twenty-six patients (32.1%) presented a total of 38 infection episodes post-KT. Induction immunosuppression with thymoglobulin, compared to basiliximab, was not associated with more infections (p = 0.8093). Patients with infectious events had lower T-cells (p = 0.0500), CD8+ T-cells (p = 0.0313) and B-cells (p = 0.0009) 1 month post-KT, compared to infection-free patients. Patients with infection also showed higher increases in TTV viral loads between week 1- month 1, post-KT, with TTV viral load variations >2.65 log10 cp/mL predicting the development of infectious events during the 12-month study period (p < 0.0001; sensitivity 99.73%; specificity 83.67%). Patients who developed de novo DSAs had lower TTV DNA viral loads at month 12 after KT, compared to patients who did not develop DSA (3.7 vs. 5.3 log10 cp/mL, p = 0.0023). Briefly, evaluating early TTV viremia is a promising strategy for defining infectious risk in the 1st year post-KT. The availability of standardized commercial real-time PCR assays is crucial to further validate this as an effective tool guiding immunosuppression prescription.